IMPLEMENTATION OF PUBLIC SERVICES IN THE ERA OF THE COVID-19 ENDEMY TRANSITION AT THE REGIONAL POPULATION AND CIVIL REGISTRATION DEPARTMENT OF TOMOHON CITY - Jeane Mantiri; Cynthia Maria Siwi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
This study aims to determine the general description of the implementation of public services in the era of the covid-19 endemic transition at the Tomohon City Population and Civil Registry Office in implementing the Tomohon e-Dukcapil online service application. This study uses a descriptive qualitative approach. Based on the results of the study, it can be concluded that the implementation of services in the Covid-19 endemic transition era with the application of online service applications by the Tomohon City Population and Civil Registry Office has not been good. It can be seen from 3 indicators, namely transparency, participation and efficiency, online application-based services have not been maximized in providing information on service progress to the community, community participation and service officers from the Tomohon City Population and Civil Registration Service. also not optimal in utilizing existing technology and services provided. It is hoped that it will be faster with the existence of information technology which has not been fully realized, this is also influenced by problems in the application of the Tomohon e-Dukcapil online service application, such as the mastery of technology from service officers and also the people who make online services still not able to run properly.